The Impact of Democratic Parenting on the Language Development of Children Aged 3–5 Years - Nurhuda Akbar; Nunuk Nurhayati (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
The first five years constitute the "golden years" of an individual's life. This peak period of development requires appropriate stimulation to achieve optimal growth. It is also a time when intelligence, skills, language abilities, and social skills are formed. A child's growth and development are influenced by various factors, including genetics and environmental elements (biological, physical, and psychosocial factors, as well as family dynamics and cultural customs). Parenting styles significantly influence child development, particularly regarding communication. Parenting practices—such as emotional attachment, verbal interaction, and the structuring of the communication environment—play a crucial role in either supporting or hindering a child's speech development. Parenting styles that lack communication or interaction can lead to difficulties in a child's speech skill acquisition. Every child grows in a unique way. Child development encompasses four domains: gross motor skills, fine motor skills, personal-social skills, and language. This study employed a cross-sectional research design with a sample size of 25 participants. The independent variable was parenting style, and the dependent variable was the child's language development. The Spearman’s rho test results yielded a value of p = 0.05 < α = 0.018, indicating a relationship between parenting style and language development in children aged 3–5 years; specifically, children raised under a democratic parenting style demonstrated superior verbal abilities compared to those raised under authoritarian or permissive styles. Consequently, the roles of both mother and father in child-rearing have a significant impact on language development. Mothers, who typically interact more frequently with their children at home, play a key role in providing language stimulation.